Reduced sterol regulatory element‐binding protein (SREBP) processing through site‐1 protease (S1P) inhibition alters oligodendrocyte differentiation in vitro. Issue 1 (2nd August 2016) - Monnerie, Hubert; Romer, Micah; Jensen, Brigid K.; Millar, John S.; Jordan‐Sciutto, Kelly L.; Kim, Sangwon F.; Grinspan, Judith B.
Abstract : The role of sterol regulatory element‐binding proteins (SREBPs), transcription factors regulating lipid synthesis, was investigated during oligodendrocyte differentiation in vitro . Blocking site‐1 protease‐induced cleavage of SREBP inhibited oligodendrocyte process growth and myelin basic protein expression, reduced expression of genes involved in lipid synthetic pathways and de novo cholesterol synthesis. This suggests SREBPs activity during oligodendrocyte maturation is required for myelin formation and integrity. Cover Image for this issue: doi:10.1111/jnc.13781 . Abstract: The formation of the myelin membrane of the oligodendrocyte in the CNS is a fundamental process requiring the coordinated synthesis of many different components. The myelin membrane is particularly rich in lipids, however, the regulation of this lipid synthesis is not understood. In other cell types, including Schwann cells, the myelin‐forming cells of the PNS, lipid synthesis is tightly regulated by the sterol regulatory element‐binding protein (SREBP) family of transcription factors, but this has not been previously shown in oligodendrocytes. We investigated SREBPs' role during oligodendrocyte differentiation in vitro . Both SREBP‐1 and SREBP‐2 were expressed in oligodendrocyte precursor cells and differentiating oligodendrocytes. Using the selective site‐1 protease (S1P) inhibitor PF‐429242, which inhibits the cleavage of SREBP precursor forms into mature forms, we found that preventing SREBP processing inhibited process growth and reduced the expression level of myelin basic protein, a major component of myelin. Further, process extension deficits could be rescued by the addition of exogenous cholesterol. Blocking SREBP processing reduced mRNA transcription and protein levels of SREBP target genes involved in both the fatty acid and the cholesterol synthetic pathways. Furthermore, de novo levels and total levels of cholesterol synthesis were greatly diminished when SREBP processing was inhibited. Together these results indicate that SREBPs are important regulators of oligodendrocyte maturation and that perturbation of their activity may affect myelin formation and integrity. Cover Image for this issue: doi:10.1111/jnc.13781 .